2021
DOI: 10.1037/men0000349
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity threat increases bias and negative emotions toward feminine gay men.

Abstract: Although acceptance of gay men has grown in recent years, gay men still regularly experience bias in their social relationships. The bias gay men experience has been theorized to stem from societal expectations regarding adherence to gender roles. Additionally, threats to masculinity have been suggested to promote antigay attitudes and discrimination among men. However, it remains unclear whether the bias gay men experience as a result of threatened masculinity is due to gay men’s sexuality, gender role adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…How might the prevailing heteronormativity in Trump's America affect heterosexual men's compassion for masculine versus feminine gay victims of hate crime? A quick look at the evidence in the literature suggests that heterosexual men, at least, would be more compassionate towards masculine than towards feminine gay men (e.g., Cohen et al., 2009; Glick et al., 2007; Herek, 2000; Laner & Laner, 1979; Wellman et al., 2021). But there are reasons to also anticipate that heterosexual men would in fact downplay compassionate expressions when it comes to the victimization of masculine gay individuals based on the social identity‐inspired reactive distinctiveness thesis (RD; Jetten & Spears, 1996, 2003; Spears et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How might the prevailing heteronormativity in Trump's America affect heterosexual men's compassion for masculine versus feminine gay victims of hate crime? A quick look at the evidence in the literature suggests that heterosexual men, at least, would be more compassionate towards masculine than towards feminine gay men (e.g., Cohen et al., 2009; Glick et al., 2007; Herek, 2000; Laner & Laner, 1979; Wellman et al., 2021). But there are reasons to also anticipate that heterosexual men would in fact downplay compassionate expressions when it comes to the victimization of masculine gay individuals based on the social identity‐inspired reactive distinctiveness thesis (RD; Jetten & Spears, 1996, 2003; Spears et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we aimed to more exhaustively test outstanding assumptions of (and address lingering questions arising from) the current investigation beyond Hypotheses 1 and 2. Firstly, Studies 1 and 2 provided supportive evidence for Hypothesis 1 (i.e., RD), but have yet to demonstrate the reality of Hypothesis 2 that we derived from FT. Why is this so, especially considering the burgeoning body of supportive findings reported for FT elsewhere in the literature (e.g., Iacoviello et al, 2019;Martínez et al, 2015;Wellman et al, 2021)? One possibility is that studies testing FT's propositions have typically manipulated a form of identity threat arising from a sense that heterosexual men are becoming too feminine (i.e., feminization anxiety), and this type of threat induction is not specific to the femininity/masculinity of the gay outgroup (see Martínez et al, 2015).…”
Section: Studymentioning
confidence: 99%
“…Some research has employed masculinity threat primes in person, including having men complete feminine tasks (e.g., hairstyling; Bosson et al, 2009), and have used the same threat cue used presently (e.g., Ching, 2022). However, other research has successfully employed this paradigm online (Wellman et al, 2021). Peyton et al (2022) also found that online experiments conducted during the pandemic produced similar findings to in-person testing.…”
Section: Discussionmentioning
confidence: 99%
“…According to the “Precarious Manhood Hypothesis,” the status of being a man and being masculine is elusive and tenuous (Vandello et al, 2008; Vandello & Bosson, 2013), which stems from masculinity being a social construct that must be earned and maintained. Unlike femininity and womanhood, typically acquired due to physiological changes during puberty, or specific life events, manhood must be earned by public displays (Vandello et al, 2008; Wellman et al, 2021).…”
Section: Minority Stressmentioning
confidence: 99%
“…Gay men are readily stereotyped as rejecting the male gender role (Madon, 1997), as feminine (Kite & Deaux, 1987) and as sexually deviant (Simmons, 1965). Some research examining gay men, has also suggested that to the extent individuals are perceived as feminine or possessing of feminine traits the less positively they are evaluated (Glick et al, 2007; Wellman et al, 2021). Given this previous literature on stereotyping and the previously discussed literature on group identification, it may suggest that highly prototypical minority group members may be ascribed more negative stereotypes of their group, not merely because they are viewed as more prototypical, but as a negative reaction to being perceived as more highly identified with their minority group identity.…”
Section: Categorization and Prototypicalitymentioning
confidence: 99%